(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The article deals with the issues of identification and analysis of sectoral threats in terms of strategic management of enterprise security. The concept of safety management is outlined and the types of threats are considered, including sectoral ones. The article describes in detail the sectoral threats that are associated with competition and collaboration between partners and consumers based on the analysis of risk factors for more than 300 enterprises. In the presentation of the strategy of security stressed that strategies for countering sectoral threats should be integrated with the company’s development strategy. In the field of security management, complex methods must be used to analyze the impact of the external environment on the organization and activities of the enterprise (for example, SWOT-analysis). However, exploitation of overly aggregated categories puts the risk of reducing the effectiveness of certain strategies to counteract threats. The impact of the environment on the system should be evaluated separately for each threat. Based on this, detailed precautionary measures are developed, which then must be correlate (co-ordinate) with the strategic development plan that ensures the coherence of the whole enterprise. Recognition and assessment of each of the threats source in an external environment is the basis of the security management strategy, which then leads to a continuous improvement of the counteraction process that negatively affects the operation of the enterprise. When creating and managing a security management strategy, attention should be payed to the system of identification and monitoring of sectoral threats. Such a system must function as an early warning system.